solve the equation,it's urgent
Attachments:
![](https://hi-static.z-dn.net/files/d40/3aa42ffb9904b0cdf5e7c777e2565f11.jpg)
Answers
Answered by
1
Answer:
g(x) = 2x+1
2x+1 = 0
x = -1/2
now p(-1/2) = 2(-1/2)^3 -11(-1/2)^2 - 4(-1/2) + 5
= 2×-1/8 -11×1/4 - 4×-1/2 + 5
=-1/4 - 11/4 - 2 +5
= -1 -11 -8 +10/4
= -10/4 = -5/2
To be a factor of f(x) its remainder should be equal to zero but here it is not.
so g(x) is not a factor of f(x)
if this helps u please mark my answer as bainliest
Answered by
1
Answer:
answer of that question
I hope it will help you
Attachments:
![](https://hi-static.z-dn.net/files/d08/64609fcddd01c8a1234ad7544e7996dd.jpg)
Similar questions
Math,
2 months ago
Environmental Sciences,
2 months ago
Social Sciences,
4 months ago
Math,
11 months ago